Hate, politics, law: critical perspectives on combating hate - Brudholm, Thomas; Johansen, Birgitte Schepelern (Studies in penal theory and philosophy, 2018)
From race to hate : a historical perspective / Erik Bleich -- Hate and the state in Ancient Greece / David Konstan -- Dwelling on hatred / Thomas Brudholm -- Problematizing hatred in democratic states / Niza Yanay -- Towards a legal concept of hatred : democracy, ontology, and the limits of deconstruction / Eric Heinze -- Criminalizing hate? / Antony R. Duff & Sandra E. Marshall -- Readdressing hate crime : synthesizing law, punishment, and restorative justice / Mark A. Walters -- Tolerance : an appropriate answer to hate? / Birgitte Schepelern Johansen -- From hate to political solidarity : the art of responsibility / Mihaela Mihai -- Democratic hatreds : the making of "the hating enemy" in liberal democracy / Mikkel Thorup -- When the state hates / Kathryn Abrams